Pengembangan kartu truth or dare interaktif berbasis canva pada materi perubahan lingkungan kelas x di SMA - Abidin, Rini; Abidinsyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop interactive Truth or Dare cards based on Canva for environmental change topics, as well as to determine their level of validity, practicality, and effectiveness in Biology learning. This research and development (R&D) study applied the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The developed product was validated by three material experts, three media experts, three language experts, and two educational practitioners. The product trial was conducted on 31 tenth-grade students of SMA Negeri 10 Banjarmasin. Data were collected using validation sheets, teacher and student response questionnaires, and learning outcomes tests consisting of a pre-test and a post-test. The results showed that the developed Truth or Dare cards obtained an average score of 79.04% in the valid category, comprising media validity of 82.66%, material validity of 71.33%, language validity of 80.66%, practitioner 1 assessment of 79.33%, and practitioner 2 assessment of 82.00%. The level of practicality based on the teacher's response was 72.00%, and the students' response was 78.83%. The product's effectiveness was demonstrated by an increase in classical learning completeness from 67.74% in the pre-test to 80.64% in the post-test. Based on these results, the Canva-based interactive Truth or Dare cards for environmental change topics meet the criteria for being valid, practical, and effective, making them feasible for use as a Biology learning medium in senior high schools.